Pengaruh Penguasaan Materi Matematika Dasar II Terhadap Penguasaan Materi Probabilitas dan Statistika - Agnesia, Yoli (LP. Ma'arif Janggan Magetan, 2022)
Basic Mathematics II is a prerequisite course for taking Probability and Statistics courses. The author found that students were constrained in solving problems in the Probability and Statistics courses because they did not master the Basic Mathematics II course material. The purpose of the study was to determine the effect of mastery of Basic Mathematics II material on mastery of Probability and Statistics material. The population of this research is the undergraduate students of Del Institute of Technology and the sample is 52 students of Bachelor of Information study program. The data used are the final grades for both courses and analyzed using simple linear regression. The results of data analysis showed that mastery of Basic Mathematics II had a significant effect on mastery of Probability and Statistics.